تكاملُ علمِ اللُّغةِ التَّطبيقيِّ والتِّقنياتِ الرَّقميّةِ القائمةِ على الكوربوس اللُّغويِّ في تجديدِ تعليمِ اللُّغةِ العربيّةِ في عصرِ الثَّورةِ الصِّناعيّةِ الرَّابعةِ - Sri Wahyuni Hidayanti; Buhori Muslim (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study aims to explain the basic concept of linguistic corpora, describe their usage, and analyze their potential in improving the quality of Arabic language learning in the era of the Industrial Revolution 4.0. This research employs a descriptive qualitative method with a literature review and interview approach. The data are analyzed using the Miles and Huberman data analysis model, which includes data reduction, data display, and conclusion drawing. The findings indicate that linguistic corpora have significant potential to support digital-based Arabic language learning in the era of the Industrial Revolution 4.0. The use of corpora not only serves as a tool for linguistic analysis but also functions as an educational innovation that can enhance students’ critical thinking skills, digital literacy, and Arabic language proficiency in a measurable and contextual manner. The implications of this study include the expansion of knowledge regarding the use of linguistic corpora in Arabic language learning and facilitating educators in implementing corpora in Arabic language teaching